2012
DOI: 10.1111/aji.12064
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexual Anal Intercourse: A Neglected Risk Factor for HIV?

Abstract: Heterosexual anal intercourse confers a much greater risk of HIV transmission than vaginal intercourse, yet its contribution to heterosexual HIV epidemics has been under researched. In this article we review the current state of knowledge of heterosexual anal intercourse practice worldwide and identify the information required to assess its role in HIV transmission within heterosexual populations, including input measures required to inform mathematical models. We then discuss the evidence relating anal interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 68 publications
1
67
0
Order By: Relevance
“…To assess the contribution of AI to transmission within heterosexual HIV and STI epidemics, information is required on frequency of heterosexual AI, with whom it is practised and whether it is condom protected [7]. Unfortunately, only 22 of 136 articles reported on condom use during AI and fewer still (N=13) reported on 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 frequency of AI, which is vital to understanding AI's contribution to HIV and other STI epidemics.…”
Section: Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the contribution of AI to transmission within heterosexual HIV and STI epidemics, information is required on frequency of heterosexual AI, with whom it is practised and whether it is condom protected [7]. Unfortunately, only 22 of 136 articles reported on condom use during AI and fewer still (N=13) reported on 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 frequency of AI, which is vital to understanding AI's contribution to HIV and other STI epidemics.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…This suggests that women may have an 18-fold higher HIV acquisition risk per UAI act compared to UVI. Even if a small fraction of all sex acts are UAI, AI may substantially contribute to HIV transmission and, at the population level, it may be as important as acute stage HIV (the first months following HIV infection, when infectivity is higher than during the asymptomatic stage) [5][6][7]. Intervention programmes that focus on reducing UAI may be easier to implement than those required to test and treat for recent infection, especially given the difficulties in identifying acute cases [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, several behavioral studies and clinical trial reports have shown that women also engage in unprotected receptive anal intercourse (RAI), with the highest rates of RAI being found among female sex workers and patients at sexually transmitted infection clinics (1)(2)(3)(4)(5)(6)(7)(8)(9). In addition, a recent metaanalysis demonstrated that the estimated per-act human immunodeficiency (HIV) transmission risk (per 10,000 exposures) for RAI is 138, compared to 11, 8, and 4 for insertive anal intercourse, receptive penile-vaginal intercourse, and insertive penile-vaginal intercourse, respectively (10).…”
mentioning
confidence: 99%
“…Maintenance of each component is essential in protecting the body from luminal contents. The rectal mucosa is considered a susceptible site for human immunodeficiency virus (HIV) transmission, with characteristics that make this site particularly vulnerable including increased numbers of HIV target cells compared to those in other parts of the gastrointestinal tract and similar to those found in the vaginal tract, with the highest numbers of target cells at the distal rectum (4)(5)(6). Defects in rectal epithelial barrier integrity and function are a concern for increased risk of transmission (4,7), with growing concern that breaches in the epithelium may facilitate pathogen translocation (8) or stimulate an immune environment which facilitates transmission (7).…”
mentioning
confidence: 99%